Body mass index and dental caries in young people: a systematic review - Martha Paisi; Elizabeth Kay; Cathy Bennett; Irene Kaimi; Robert Witton; Robert Nelder; Debra Lapthorne (BMC, 2019)
Abstract Background Obesity and caries in young people are issues of public health concern. Even though research into the relationship between the two conditions has been conducted for many years, to date the results remain equivocal. The aim of this paper was to determine the nature of the relationship between Body Mass Index (BMI) and caries in children and adolescents, by conducting a systematic review of the published literature. Methods A systematic search of studies examining the association between BMI and caries in individuals younger than 18 years old was conducted. The electronic bibliographic databases PubMed, MEDLINE, Embase, CINAHL, CENTRAL and Google Scholar were searched. References of included studies were checked to identify further potential studies. Internal and external validity as well as reporting quality were assessed using the validated Methodological Evaluation of Observational Research checklist. Results were stratified based on the risk of flaws in 14 domains 10 of which were considered major and four minor. Results Of the 4208 initially identified studies, 84 papers met the inclusion criteria and were included in the review; conclusions were mainly drawn from 7 studies at lower risk of flaws. Three main types of association between BMI and caries were found: 26 studies showed a positive relationship, 19 showed a negative association, and 43 found no association between the variables of interest. Some studies showed more than one pattern of association. Assessment of confounders was the domain most commonly found to be flawed, followed by sampling and research specific bias. Among the seven studies which were found to be at lower risk of being flawed, five found no association between BMI and caries and two showed a positive association between these two variables. Conclusions Evidence of an association between BMI and caries was inconsistent. Based on the studies with a low risk lower risk of being flawed, a positive association between the variables of interest was found mainly in older children. In younger children, the evidence was equivocal. Longitudinal studies examining the association between different indicators of obesity and caries over the life course will help shed light in their complex relationship.